2013
DOI: 10.4314/tjpr.v11i6.7
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Extract of <i>Myelophycus caespitosus</i> Inhibits the Inflammatory Response in Lipopolysaccharidestimulated BV2 Microglial Cells by Downregulating NF-kB via Inhibition of the Akt Signaling Pathway

Abstract: Purpose: To determine whether the methanol extract of Myelophycus caespitosus (MEMC) downregulates the expression of pro-inflammatory mediators in lipopolysaccharide (LPS)-stimulated BV2 microglial cells. Methods: Reverse transcription-polymerase chain reaction (RT-PCR) together with Western blot analysis was used to evaluate the expression of pro-inflammatory mediators such as nitric oxide (NO) and prostaglandin E2 (PGE2) as well as their regulatory genes such as inducible NO synthase (iNOS) and cyclooxygenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Fucoidan from the alga Polyopes affinis suppressed the formation of PGE2 and NO through inhibition of the expression of corresponding genes in microglial BV2 cells, stimulated by LPS , and also inhibited IFNα in glial cells .…”
Section: The Influence Of Sulfated Polysaccharides On Inflammatory Prmentioning
confidence: 96%
“…Fucoidan from the alga Polyopes affinis suppressed the formation of PGE2 and NO through inhibition of the expression of corresponding genes in microglial BV2 cells, stimulated by LPS , and also inhibited IFNα in glial cells .…”
Section: The Influence Of Sulfated Polysaccharides On Inflammatory Prmentioning
confidence: 96%
“…Although we have reported that a methanol extract of M. caespitosus (MEMC) has potent anti-inflammatory effects in BV2 microglial cells (Jayasooriya et al, 2012), scientific evidence for the pharmacological efficacy of M. caespitosus, including its antioxidant properties, is very limited. Therefore, the objective of the present study was to investigate the antioxidant capacity of MEMC against oxidative stress-mediated cytotoxicity in muscle cells.…”
Section: Introductionmentioning
confidence: 99%